Efektivitas model kooperatif tipe Team Assisted Individualization (TAI) terhadap pembelajaran matematika - Pratiwi, Anting (ARKA INSTITUTE, 2022)
This study aims to determine the effectiveness of the application of mathematics learning through the Team Assisted Individualization (TAI) type of cooperative learning model. This type of research is an experiment involving one class as an experimental class without a control class, and the research design used is One Group Pretest Posttest Design. The sample in this study was grade IV students for the 2021/2022 academic year as many as 20 people. The instrument used is a test of learning outcomes to observe student activities. The results showed that: (1) the average score of students' mathematics learning outcomes after the TAI type cooperative learning model was in the medium category and classical mastery was achieved. (2) the average percentage of student activity frequency has reached the active criteria. From the results of this study, it can be concluded that the Team Assisted Individualization (TAI) type of cooperative learning model is effectively applied in learning mathematics for fourth grade students.